(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article presents the results of research conducted in 2023 to evaluate the average indicators of certain morphological traits of the new medium-fiber cotton variety “Kelajak-3”, developed by breeders of the Republic of Uzbekistan. The traits studied included plant height, number of fruiting branches, branching type, and number of locules in bolls. These indicators were compared with the standard varieties Namangan-77 and S-6524. The results showed that under the conditions of the experimental field in the Tashkent region, the average plant height of the Kelajak-3 variety was 82.5 cm, the number of fruiting branches was 12.2, the branching type was 1.99, and the number of locules in bolls was 4.72.